(NtWORI W (B5-(NTI TOMAH (B/s (Nt(B. 2,s (NpOEZ)QÆÇ (B/s)E - (NmALI[KO(B, (NaNDR)QÆJs)E; (N{WEC(B, (Nw(B. (Ns(B.,s; (NmALI[KO(B, (NaNDR)QÆJs)E ((NkI)QÇW (B:s)E (NdN)QÆPRO(B,s)E, 1987)
(Nu DRUGOMU TOM)QÆ (B- (NKRA]Æ WÆR[Æ ZÆ ZBÆROK (B"(NbITWA(B" (1943), "(NqROSLAWNA(B" (1946), (NTA POEMI (B"(NpROMETEJ(B", "(NsINI(B", "(NvIWA LEGENDA(B" (NTA ÆN[Æ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NpOEZ)QÆÇs)E